Upaya Penurunan Kecacatan Produk dan Perancangan Monitoring Proses Produksi di CV Jamatex - Raoulian Witarto Tjandra; Herry Christian Palit (Jurnal Titra, 2023)
CV Jamatex is a company engaged in the textile industry. One of the products produced by CV Jamatex is a patterned rayon fabric. The high level of defects and the absence of monitoring of the production process are the two biggest obstacles experienced by CV Jamatex. In the analysis of the problem for a high level of defects in this report, there are four types of defects, namely the types of defects in the rayon fabric which are stained, faded, torn and dirty. To analyze the level of disability is done using the five whys analysis method. For these four types of defects, improvement plans have been made, in the form of form printing worksheets, machine maintenance worksheets, work instructions, and prototype stenter machine aids. Whereas for problem analysis there is no monitoring of the production process, this is because monitoring at CV Jamatex is still quite simple. The design of the improvements made is to monitor the production process through the Microsoft Excel platform. The design of improvements in this final project report aims to overcome two problems that occur at CV Jamatex. The company has validated the proposed improvements.